Simultaneous Determination of Eight Preservatives in Feeds by High Performance Liquid Chromatography - Gao, Wen-Hui; Cao, Xiao-Mei; Han, Jun-Hua; Li, Xing-Feng; Jia, Ying-Min (Asian Journal of Chemistry, 2014)
A high performance liquid chromatography method for the separation and determination of eight preservatives benzoic acid, sorbic acid and six parabens in feeds was developed and validated. The condition of sample preparation was 50 % methanol and 50 % water (v/v) extraction of the feeds. The experiment was carried out with the mobile phase of methanol-0.05 mol/L ammonium formate aqueous solution (pH 4.5) using gradient elution at 245 nm. Under optimized conditions, the eight preservatives were separated successfully within 13 min. The correlation coefficients were more than 0.9991 and the detection limits were in the range of 0.05 and 0.5 μg/mL. The average recoveries of the eight preservatives were between 80.8 and 107.4 %. The relative standard deviations (RSDs) were less than 5.0 % (n = 5). The proposed HPLC method is sensitive, reliable, fast and can be applied to quality control test of preservatives in feeds.